The Cash Flows Impact on the Financial Performance of Romanian Retail Companies - Lucian Gabriel MAXIM (Dunarea de Jos University of Galati, 2021)
The study makes an analysis of the cash flow impact on the profitability of companies in the field of retail in Romania. The study involved a survey conducted on a number of 62 companies, the data were taken from the annual balance sheets published by the companies concerned and which were centralized and exported using the TPSoft website. The data were processed and analysed using the multiple regression technique for panel data. The research results revealed that the operational cash flow has a statistically significant positive effect (99.9% confidence) on the profitability of companies in this field, a performance represented by the net profit obtained. It was also observed that cash flows from financing and investments have a negative but significant relationship with corporate profitability.